2019
DOI: 10.1021/jacs.8b12483
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of the Orientational Anisotropy of Buried Hydroxyl Groups inside Muscovite Mica

Abstract: Muscovite mica (001) is a widely used model surface for controlling molecular assembly and a common substrate for environmental adsorption processes. The mica (001) surface displays near-trigonal symmetry, but many molecular adsorbatesincluding waterexhibit unequal probabilities of alignment along its three nominally equivalent lattice directions. Buried hydroxyl groups within the muscovite structure are speculated to be responsible, but direct evidence is lacking. Here, we utilize vibrational sum frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 60 publications
1
27
0
1
Order By: Relevance
“…They concluded that, as the humidity increases, the sub‐monolayer water structure evolves into a more ordered D‐bonding network with the complete absence of the free‐OD peak at full monolayer coverage. Another SFG study employing the SA geometry demonstrated an azimuthal angle dependence of the OH‐stretch response at mica (001), which indicated the mica crystal structure imposes anisotropy on the interfacial water response [64] . As discussed in more detail in Section 8.2.2, several groups [65] have studied the mica–water interface in the context of ice nucleation, concluding that the surface‐induced ordering of water plays an important role in the freezing process of water.…”
Section: Micamentioning
confidence: 99%
“…They concluded that, as the humidity increases, the sub‐monolayer water structure evolves into a more ordered D‐bonding network with the complete absence of the free‐OD peak at full monolayer coverage. Another SFG study employing the SA geometry demonstrated an azimuthal angle dependence of the OH‐stretch response at mica (001), which indicated the mica crystal structure imposes anisotropy on the interfacial water response [64] . As discussed in more detail in Section 8.2.2, several groups [65] have studied the mica–water interface in the context of ice nucleation, concluding that the surface‐induced ordering of water plays an important role in the freezing process of water.…”
Section: Micamentioning
confidence: 99%
“…Muscovite with this surface termination has been used in several studies. [41][42][43][45][46][47] No water is considered in the present study, although it would certainly affect the results, for example via the solvation of the K + ions.…”
Section: Simulation Set Upmentioning
confidence: 99%
“…To probe interfaces, several surface-specific techniques can be used such as environmental scanning electron microscopy (ESEM), secondary ion mass spectrometry (SIMS), Auger electron spectroscopy (AES), etc. 42 46 One method, vibrational sum-frequency generation (vSFG), 47 , 48 has received a lot of attention for characterizing interfaces experimentally 49 57 and in conjunction with simulations. 51 , 52 , 58 62 The synergy between vSFG experiments and molecular simulations allows for an in-depth probing of the interface, permitting a finer molecular interpretation of the underlying interfacial region.…”
Section: Introductionmentioning
confidence: 99%